2018
DOI: 10.2478/amma-2018-0011
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Density Gradient Centrifugation Protocol for Isolation of Peripheral Blood Mononuclear Cells

Abstract: Objective: Peripheral blood mononuclear cells (PBMC) are extremely important in the body's immune response. Their isolation represents a major step in many immunological experiments. In this two phase study, we aimed to establish an optimum protocol for PBMC isolation by density-gradient centrifugation. Methods: During Phase-1, we compared two commercially available PBMC isolation protocols, Stemcell Technologies (ST) and Miltenyi Biotec (MB), in terms of PBMC recovery and purity. Twelve blood samples were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
7
1
Order By: Relevance
“…Using the same isolation and viability staining protocols, we have previously shown that the post-isolation viability of monocytes is low (17%), while lymphocytes have very high viabilities (86-91%) (30). However, in the present study, we report an average post-isolation viability of only 82%.…”
Section: Viability and Cytokine Synthesiscontrasting
confidence: 55%
See 3 more Smart Citations
“…Using the same isolation and viability staining protocols, we have previously shown that the post-isolation viability of monocytes is low (17%), while lymphocytes have very high viabilities (86-91%) (30). However, in the present study, we report an average post-isolation viability of only 82%.…”
Section: Viability and Cytokine Synthesiscontrasting
confidence: 55%
“…Isolation and activation of PBMC Isolation of PBMC was performed using an already tested protocol for which we have previously reported high yields of 90% for 3mL blood samples (30). Nevertheless, our subsequent experience with PBMC density gradient isolation (this study included) showed us that processing blood volumes higher than 3mL will in fact significantly lower the cell yield.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Blood samples were processed within 2hrs from collection. PBMCs were isolated using a high-yield density gradient centrifugation protocol that was already tested and implemented in our laboratory [17]. In between the centrifugation steps, cells were resuspended in complete RPMI medium (cRPMI) consisting of: RPMI 1640 culture medium Sigma Aldrich (Cat.…”
Section: Pbmc Isolationmentioning
confidence: 99%